TINGKAT KETERLAKSANAAN PENDEKATAN SAINTIFIK PADA MATA PELAJARAN IPA BERBASIS KURIKULUM 2013 MENURUT PERSEPSI SISWA KELAS IX SMP NEGERI PEKANBARU - Husnul Mar’ati Wulandari; Azhar '; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to describe the level of implementation scientific approach in science based on Curriculum 2013 according to the perception of 9th grade student of SMP Negeri Pekanbaru. The research use survey method. The population is students of 9th grade SMP Negeri Pekanbaru, namely: SMPN 1 Pekanbaru, SMPN 6 Pekanbaru, and SMPN 23 Pekanbaru the totally is 771 students. The sample use Slovin with the error level is 5% of the population, while the sample is 263 students. The results of research the level of implementation scientific approach in science based on Curriculum 2013 according to the perception of 9th grade student of SMP Negeri Pekanbaru the score is 2.73 in the category quite well. It can be concluded that the application of the scientific approach to the learning process at schools with the maximum has not been done. It is caused by several factors, namely: the limited time, limited infrastructure such as infocus in the classroom, the teacher is less a creative learning.Key Words: The Nature Of Learning Physics, Curriculum 2013, Scientific Approach